Assessing Australian Monetary Policy in the Twenty‐First Century. Issue 322 (13th June 2022) - Gross, Isaac; Leigh, Andrew
Abstract : Using the Reserve Bank of Australia's MARTIN model, we compare actual monetary policy decisions with a counterfactual in which the cash rate is set according to an optimal simple rule. We find that monetary policy played a crucial role in avoiding a potential recession in 2001 and mitigating the downturn in 2008–09. By contrast we find that the cash rate was too high during 2016–19, keeping inflation below the Reserve Bank's target band. Optimal monetary policy in 2016–19 would have involved a substantially lower cash rate and produced significantly better employment outcomes.